Inequality, Taxation, and Intergenerational Transmission - Bishop, John A. (Research on Economic Inequality Ser., 2018)
Research on Economic Inequality, volume 26, primarily contains papers presented at the 8th Society for the Study of Economic Inequality (ECINEQ) meeting. The papers cover such topics as the effect of inheritance taxation on the ""pre-distribution"" of income, and tax progressivity under alternative inequality definitions.